The Gentle Art of Retroduction: Critical Realism, Cultural Political Economy and Critical Grounded Theory. Issue 2 (February 2017) - Belfrage, Claes; Hauf, Felix
This article, first, proposes critical grounded theory (CGT) as a way to develop systematically an array of methods and theoretical propositions into a coherent critical methodology for organization studies (and beyond). Second, it demonstrates CGT's usefulness through a case study of competing recovery projects from the Icelandic financial crisis. CGT is developed in engagement with the emerging paradigm of cultural political economy (CPE) and its preferred method of critical discourse analysis (CDA). CPE analyses the evolution of 'economic imaginaries' in both their structural/material and semiotic/discursive dimensions. This requires a critical realist, multi-dimensional research strategy which emphasizes ethnographic methods and substantial theoretical and historical work. The proposed methodology of CGT enables a retroductive research process that combines deductive theoretical deskwork with inductive fieldwork enabled by grounded theory tools to analyse organizational process, stability and change.